Associação entre o polimorfismo rs2275913 de IL-17 e a gravidade da bronquiolite aguda em lactentes - Mocellin, Magáli (2014)
Introduction: acute viral bronchiolitis (AVB) is a respiratory infection of high incidence in infants. The mechanisms associated with the severity of the disease are poorly understood. Its severity may be associated with genetic and immunological factors. Some mediators of the immune response appear to influence the response to the virus, especially interleukins (IL). IL-17 is a pro-inflammatory cytokine present in the tracheal aspirates from patients with AVB. This interleukin induces the expression of other pro-inflammatory cytokines, and migration of neutrophils. The objective of the study was to determine if IL-17 gene variations are associated with the severity of AVB. Methods: in the present study we recruited infants admitted in the pediatric emergency in the Hospital São Lucas (HSL) PUCRS diagnosed with AVB and younger than 12 months of age, from September 2009 to September 2011; and infants without hospitalization selected at the primary health care center (CSBJ) in Porto Alegre. Capillary blood samples were collected and DNA was extracted for genotyping of single nucleotide polymorphism (SNP rs2275913 of the IL -17 gene). Results: participated in the final analysis of this genetic association study 121 cases and 71 controls. The rare allele of SNP rs2275913 of IL -17 showed a protective effect for severe AVB, with higher frequency of homozygous AA (14.1% vs 5.8%; p = 0.047) in the control group (without hospitalization). The risk of G carriers for severe bronchiolitis was 2.7 times greater. Conclusion: the study suggests that the polymorphism rs2275913 of IL -17 is associated with protection of AVB and can directly influence the severity of AVB these children. This variation may be a marker to identify high risk patients.